Alternative modulation of protein–protein interactions by small molecules. (December 2015) - Fischer, Gerhard; Rossmann, Maxim; Hyvönen, Marko
Graphical abstract: Highlights: Protein–protein interactions can be modulated by more than orthosteric disruption. Modulator categories: 'orthosteric versus allosteric' and 'disrupting versus stabilising'. Interfacial binders exert secondary effects. Non-competitive modulation is a way around low affinity molecules. Non-competitive modulators require tailored screening strategies. Abstract : Protein–protein interactions (PPI) have become increasingly popular drug targets, with a number of promising compounds currently in clinical trials. Recent research shows, that PPIs can be modulated in more ways than direct inhibition, where novel non-competitive modes of action promise a solution for the difficult nature of PPI drug discovery. Here, we review recently discovered PPI modulators in light of their mode of action and categorise them as disrupting versus stabilising, orthosteric versus allosteric and by their ability to affect the proteins' dynamics. We also give recent examples of compounds successful in the clinic, analyse their physicochemical properties and discuss how to overcome the hurdles in discovering alternative modes of modulation.